Natural Dyes as a Photosensitizer from Dragon Fruit (Hylocereus polyrhizus) for Dye-Sensitized Solar Cells - Kartika Sari; Sunardi sunardi; Dita Asa Panunggul; Agung Bambang Setio Utomo; Parmin Lumban Toruan; Ampala Khoryanton (Politeknik Negeri Lhokseumawe, 2023)
Natural Dye is one of the important materials of DSSC which absorbs photons from the sun’s rays and transmits the photoelectron. One of the natural dyes is Dragon fruit dye. The characterization of the optical and electrical properties of a sensitizer DSSC used a UV-Vis spectrometer, FTIR spectrometer, and solar power meter. The absorption spectra of the UV-Vis spectrometer are being measured by a wavelength range of 400 – 700 nm and show a maximum peak of 535 nm. The result of the FTIR spectrometer shows the functional group of H-bond stretching, C=O, and C-O-H stretching vibrations. It is a part of anthocyanin and chlorophyll. Zinc Oxide (ZnO) paste coated on the Indium Tin Oxide (ITO) as the thin film is dipped in the Dragon fruit dye extracted for 30 hours. Thin film is prepared as the working electrode and counter electrode. The characteristic of current and voltage (I-V) as electrical properties are measured by the solar power meter. The result of the current and voltage DSSC from Dragon fruit dye extracted coated ZnO obtained, indicated that the energy bandgap could be optimized to make a wide bandgap. ZnO thin film needs the Dragon fruit dye to decrease the surface and move electrons in the bandgap. The Dragon fruit dye extracted coated ZnO thin film could be used as a sensitizer since it will increase the correlation between the ZnO thin film and dye. And the last, it will improve the quality of solar cells as well.